Rethinking America’s Past: Howard Zinn’s A People’s History of the United States in the Classroom and Beyond - Winslow, Barbara (Radical Teacher, 2023)
Review of Robert Cohen, and Sonia Murrow, Rethinking America’s Past: Howard Zinn’s A People’s History of the United States in the Classroom and Beyond.